Aminopropyl functionalization of superparamagnetic iron oxide/SiO2 nanocrystals for adsorption of bisphenol A from water. Issue 56 (1st December 2016) - Farmany, A.; Shirmohammadi, M.M.; Kazemi, S.; Hatami, M.; Mortazavi, S.S.
Abstract: Iron oxide nanocrystals synthesized by a co-precipitation method were decorated with an aminopropyl functionalized silica layer and characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. Surface area of nanocrystals was measured using the N2 adsorption–desorption Brunauer-Emmet-Teller procedure. Large surface area (208.0 m 2 /g) of nanocrystals confirmed their potential for adsorption of organic/inorganic material. So the nanocrystals were used for adsorption of Bisphenol A (BPA) from aqueous solutions. As a continuation, the influence of different parameters including adsorbent dosage, pH, temperature, and ionic strength on the removal efficiency of BPA was studied. The experimental data were fitted well with the pseudo-second-order kinetic model ( R 2  = 0.99). The adsorption isotherm was described well by the Freundlich isotherm.